The complex relationship between personal sense of connection to animals and self‐reported proenvironmental behaviors by zoo visitors. Issue 2 (24th January 2017) - Grajal, Alejandro; Luebke, Jerry F.; Kelly, Lisa‐Anne DeGregoria; Matiasek, Jennifer; Clayton, Susan; Karazsia, Bryan T.; Saunders, Carol D.; Goldman, Susan R.; Mann, Michael E.; Stanoss, Ricardo
Abstract: The global biodiversity crisis requires an engaged citizenry that provides collective support for public policies and recognizes the consequences of personal consumption decisions. Understanding the factors that affect personal engagement in proenvironmental behaviors is essential for the development of actionable conservation solutions. Zoos and aquariums may be some of the only places where many people can explore their relations with wild animals and proenvironmental behaviors. Using a moderated‐mediation analysis of a survey of U.S. zoo and aquarium visitors ( n = 3588), we explored the relationship between the sense of connection to animals and self‐reported engagement in proenvironmental behaviors related to climate change and how this relationship is affected by certainty that climate change is happening, level of concern about climate change, and perceptions of effectiveness in personally addressing climate change. We found a significant, directional relationship between sense of connection to animals and self‐reported proenvironmental behaviors. Political inclination within the conservative to liberal spectrum did not affect the relationship. We conclude that a personal sense of connection to animals may provide a foundation for educational and communication strategies to enhance involvement in proenvironmental actions.